Autonomous Underwater Glider: A Comprehensive Review - Enrico Petritoli; Fabio Leccese (Drones)
A comprehensive review of Autonomous Underwater Gliders encompasses their development, technological advancements, operational principles, and applications in various fields. It explores the different types of architectures, such as those with blended wing or conventional designs, and examines their roles in scientific research and civil use. The review also addresses the challenges and limitations in areas like payload, navigation, swarm management, and the effects of underwater environments on glider performance. This knowledge is essential for improving glider technology and expanding their potential in future underwater exploration and data collection missions.